CORRELATION BETWEEN THE INTERNAL ELEMENTS OF THE CORPORATE SOCIAL RESPONSIBILITY CONCEPT (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
The concept and practice of Corporate Social Responsibility (CSR) relates to the entire range of the company’s activities which include internal and external relations with the environment. Positive and proactive activities of the companies in CSR implementation became common practice in developed countries, mostly due to the benefits for all involved stakeholders. Implementation of CSR is very demanding because of its complexity. It demands a combination of different elements on an internal and external level. Therefore, it is important to see if there is a correlation between those elements with a focus on internal CSR elements.The theoretical part gives a review of relevant sources with the aim to create a framework for understanding the correlation between different elements of CSR. Research was conducted in the period from the beginning of February to mid-June 2018 in four companies from the food processing industry. Companies were in the category of small, medium and large. The sample included fifty employees of four companies. A highly structured questionnaire included four areas of study: the working environment, environment protection, relations with local community and strategic guidelines. The collected data were statistically processed with IBM SPSS 22 and IBM SPSS Amos 22 by using standard statistical methods. The research question was is there a correlation between the four selected internal CSR elements.Research results may be used for better CSR implementation on the internal level within the companies because it confirmed a strong correlation between the four selected internal CSR elements. Therefore, the implementation process within the companies must focus evenly on these four internal CSR elements in order to gain a positive effect.